2023
DOI: 10.1039/d2im00056c
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent catalyst design for CO2/N2/NOxelectroreduction

Abstract: Electroreduction of small molecules such as CO2, N2, and NO3- is one of the promising routes to produce sustainable chemicals and fuels and store renewable energy, which could contribute to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 81 publications
1
3
0
Order By: Relevance
“…The slight decrease in the CP-O formation yield was attributed to the coherent higher pH of the NO 2 – solution, which is not favorable to the reduction of NO x because the reaction requires active hydrogen species produced by water. It suggests that this process has the potential to be coupled with upstream technologies enabling sustainable nitrogen chemistry such as air nonthermal plasma oxidation and nitrification of bacteria, which was traditionally utilized in ammonia synthesis. By utilizing K 15 NO 3 as the reactant, we observed a molecular ion peak of the product at 99.9 (Figure S32), which precisely corresponds to the calculated weight of C 5 H 9 15 NO. The result confirms that the nitrogen in CP-O originates from the nitrate.…”
Section: Resultssupporting
confidence: 53%
“…The slight decrease in the CP-O formation yield was attributed to the coherent higher pH of the NO 2 – solution, which is not favorable to the reduction of NO x because the reaction requires active hydrogen species produced by water. It suggests that this process has the potential to be coupled with upstream technologies enabling sustainable nitrogen chemistry such as air nonthermal plasma oxidation and nitrification of bacteria, which was traditionally utilized in ammonia synthesis. By utilizing K 15 NO 3 as the reactant, we observed a molecular ion peak of the product at 99.9 (Figure S32), which precisely corresponds to the calculated weight of C 5 H 9 15 NO. The result confirms that the nitrogen in CP-O originates from the nitrate.…”
Section: Resultssupporting
confidence: 53%
“…Furthermore, there should be a specific focus on enhancing the downstream processes of product separation and purification to ensure the practical viability of NO x ‐involving reactions [62–63] . Recent studies demonstrated the successful implementation of separation and purification strategies.…”
Section: Discussionmentioning
confidence: 99%
“…[61] Furthermore, there should be a specific focus on enhancing the downstream processes of product separation and purification to ensure the practical viability of NO xinvolving reactions. [62][63] Recent studies demonstrated the successful implementation of separation and purification strategies. For example, Wang and colleagues showcased the effectiveness of the air stripping method in collecting highpurity ammonia products.…”
Section: Catalyst-solution-cell Multiscale Systemmentioning
confidence: 99%
“…[9][10][11][12][13][14] Researchers have developed the electrochemical conversion of CO 2 into value-added chemicals, including CO, formic acid, ethylene and ethanol. [15][16][17][18][19][20][21] Besides, recent studies have also demonstrated the electrochemical synthesis of ammonia from N 2 or NO x . 22,23 The performance of the electrochemical conversion of CO 2 /N 2 /NO x relies on several factors, such as the selection of electrode materials, the type of electrolyte, and the modification of the electrolytic cell.…”
Section: Introductionmentioning
confidence: 99%